How Do Social Media Marketing Activities Result in Online Purchase Decisions - Farah Putri Wenang Lusianingrum (UNIVED Press, 2023)
The main focus of this study is to explain the mechanism of how social media marketing activities can produce online purchasing decisions. This condition is related to the trend of marketers in the skincare business in Indonesia using social media for marketing activities. The current phenomenon is that social media is a means for marketing and a sales median. This research uses a survey method carried out by distributing questionnaires online. Determination of the sample in this research was carried out using a convenience method approach. 180 data were collected, but only 174 could be analyzed using Smart PLS software. The analysis results show that the proposed model based on the Stimulus (social media marketing activity) - Organism (brand awareness and brand trust) - Response (online purchasing decision) mechanism is accepted. This research model proposes four hypotheses, and all of them are accepted. Social media marketing activities as a stimulus have been proven to influence brand awareness and brand trust (organism). Furthermore, brand awareness and trust influence online purchasing decisions for SOMETHINC products (response).